Demorest Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1883)
Demorest's Family Magazine. January 1883. Vol. 19, No. 3. -- That Jolly Old Couple -- In Charge of the Captain -- Twenty-One -- White Chrysanthemum -- Miss Clifton's New Year -- John Wilson's Love -- The Ancient Greek Sport Kottabos -- The Raven and Snowman -- Holiday Gifts and Customs in Paris -- Forgotten by the World -- Agnes Bernauer -- The Admiral's Ward -- My Grandmother's Story -- Household -- Home Art and Home Comfort -- Child-Life in Paris -- How We Live in New York -- A Public Nuisance -- The Fisher Boy and the Fisherman's Daughter -- The Bravery of Women -- What Women are Doing -- Current Topics -- Kitchen -- Spice Box -- Mirror of Fashions -- Ladies' Club -- Review of New Publications
Mme Demorest's Mirror of Fashions
New York Illustrated News
Digitized from original print, Valdosta State University Archives and Special Collections, November 21, 2017.
Keywords: Demorest's Family Magazine; Magazine; Illustrated Periodicals; Periodicals; Travel; Dressmaking; Homemaking; Needlework; Women; Catalogue; Children; Social History; Women's History; Fashion; United States; 1800s; 19th Century